2021
DOI: 10.1002/adem.202100237
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Hot Gas Corrosion of Al–Cr–Fe–Ni‐Based High‐Entropy Alloys with Addition of Co and Mo

Abstract: Multicomponent, high‐entropy alloys (HEAs) are promising candidates for replacing conventional alloys in high‐temperature applications. Herein, the high‐temperature corrosion of AlCrFeNiX0.5 (X = Co, Mo) is investigated. The samples are tested for their oxidation resistance at temperatures up to 1200 °C for 120 h and their behavior in NaCl/Na2SO4 at 900 °C for 96 h. They are benchmarked against commercial alloys such as FeCrAl. Despite the same contents of Al and Cr, the HEAs form different oxide layers showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Table 2 displays the possible oxidation rates with the corresponding rate constants obtained after fitting. Previous studies have shown that the oxidation of AlCoCrFeNi HEAs follows parabolic rate laws [65]. In summary, the oxidation resistance of AlCoCrFeNi HEAs during isothermal oxidation tests is highly dependent on both temperature and time.…”
Section: Microstructural Evolutionmentioning
confidence: 71%
“…Table 2 displays the possible oxidation rates with the corresponding rate constants obtained after fitting. Previous studies have shown that the oxidation of AlCoCrFeNi HEAs follows parabolic rate laws [65]. In summary, the oxidation resistance of AlCoCrFeNi HEAs during isothermal oxidation tests is highly dependent on both temperature and time.…”
Section: Microstructural Evolutionmentioning
confidence: 71%
“…The presence of Cr and Al aids in forming an oxide layer on the surface of the alloy, which helps hinder the direct contact between oxygen and the metal. [6][7][8] The oxidation scale includes Al 2 O 3 when the Al content is sufficient (4-6 wt%) because of the lower partial pressure of dissociated oxygen for Al 2 O 3 compared to that in Cr 2 O 3 . [9][10][11][12] Both Al and O diffuse through short-circuit diffusion, and therefore, they are considered grain boundaries on the Al 2 O 3 scale.…”
Section: Introductionmentioning
confidence: 99%
“…When the addition amount of these elements in the alloy reaches a certain value, a protective oxide film will be formed on the alloy surface, which will improve the high-temperature oxidation resistance of the alloy. [3][4][5] Some Y, La, Ce, and other rare earth elements will also play some special roles in the high-temperature oxidation process of the alloys. [6,7] Sun [8] found that the addition of Al will form a composite oxide of Al and Si at the external oxide film/ matrix during the oxidation process at 1200°C, which can effectively inhibit the phase diffusion of alloy oxidation reaction components, so as to reduce the initial oxidation rate of Ni-20Cr-Si alloy.…”
Section: Introductionmentioning
confidence: 99%